Non‐small cell lung carcinomas with diffuse coexpression of TTF1 and p40: clinicopathological and genomic features of 14 rare biphenotypic tumours. Issue 2 (20th October 2022) - Savari, Omid; Febres‐Aldana, Christopher; Chang, Jason C.; Fanaroff, Rachel E.; Ventura, Katia; Bodd, Francis; Paik, Paul; Vundavalli, Murty; Saqi, Anjali; Askin, Frederic B.; Travis, William D.; Rekhtman, Natasha
Abstract : Thyroid transcription factor 1 (TTF1) and p40 are widely‐utilized diagnostic markers of lung adenocarcinoma (LUAD) and squamous cell carcinoma (LUSC), respectively. Diffuse coexpression of TTF1 and p40 has been described in only rare case reports. In a multi‐institutional study, we collected the largest cohort of these unusual tumours to‐date ( n  = 14), with the goal of elucidating their clinicopathological and genomic characteristics. Lung tumours with diffuse coexpression (labelling 50–100% tumour cells) of TTF1 clone 8G7G3/1 and p40 clone BC28 were identified. Detailed clinicopathological and immunohistochemical parameters were analyzed. Eight tumours were analyzed by next‐generation sequencing (NGS) and the results were compared to those in > 9 K LUAD and > 1 K LUSC. All tumours with diffuse TTF1/p40 coexpression were poorly differentiated non‐small cell lung carcinomas (NSCLC), 42% of which had basaloid features. Some tumours exhibited focal keratinization (14%), napsin A and/or mucicarmine labelling (46%) or both squamous and glandular features (7%). NGS revealed a uniquely high rate of FGFR1 amplifications (70%) compared to either LUAD (0.7%, P  < 0.0001) or LUSC (11%, P  = 0.001). LUAD‐type targetable driver alterations were identified in 38% of cases (one EGFR, two KRAS G12C). The tumours were clinically aggressive, exhibiting metastatic disease in most patients. Lung carcinomas with diffuse TTF1/p40 coexpression represent poorly differentiated NSCLCs with frequent basaloid features, but some show evidence of focal squamous, glandular or dual differentiation with a distinctly high rate of FGFR1 amplifications. The presence of targetable LUAD‐type alterations ( EGFR, KRAS G12C) emphasizes the importance of molecular testing in these tumours. Abstract :